Transurethral resection of the prostate a 3 year experience - N O Chukwujama (Nigerian Journal of Surgery, 2011)
Background: Transurethral resection of the prostate (TURP) is considered the ′gold standard′ in the surgical management of bladder outlet obstruction secondary to benign prostatic hyperplasia and advanced carcinoma of the prostate. The procedure is however still not routinely available in most public health institutions in Nigeria. We present our experience with this treatment modality over a three year period Methods: The records of patients who underwent TURP over a period of three years (April 2006 May 2009) were examined. The biodata, Laboratory investigations, detail of the surgical procedure and outcome were extracted and analysed. Results: The records of forty three patients were examined. The age range was 49 76yrs (mean 65yrs +/- 5.8 SD). The prostate specific antigen ranged from 1.3 50.3ng/ml (mean 13.3 +/- 12.8). The mean prostate size was 59g +/- 20 SD (range 27 98grams). The indications for the surgery included refractory acute urinary retention 48.8%, failed medical treatment 21%, recurrent UTI 16%, recurrent haematuria 9%, chronic urinary retention 2%. The mean duration of surgery was 80.5mins +/- 14 SD (range 60 120mins). The period of hospital stay ranged from 3 32 days (mean 8.7 days +/- 7.7 SD). Complications included capsular perforation in 2 patients, TURP syndrome in 2 patients, total incontinence in 1 patient and failure to void in 2 patients. Most patients (93%) had satisfactory voiding and insignificant post void residual urine volume during subsequent follow up visits Conclusion: Transurethral resection of prostate is a safe and effective treatment modality in the surgical management of men with bladder outlet obstruction secondary to BPH and advanced CAP in our environment.